a)
sqrt((2+sin(2*u))^2 + (1)^2)*sin(v)
Y=u
Z=sqrt((2+sin(2*u))^2 + (1)^2)*cos(v)
0<=u<=2*pi
0<=v<=4*pi
X=2+sin(2*u)
Y=u
Z=1
rotiranje oko Y ose
0<=u<=2*pi
b)
X=(4*pi - v)/(4*pi - 0) * sin(2+u) + (u - 0)/(2*pi - 0) * 2*v*sin(v)
Y=(4*pi - v)/(4*pi - 0) * u + (u - 0)/(2*pi - 0) * 1
Z=(4*pi - v)/(4*pi - 0) * 1 + (u - 0)/(2*pi - 0) * v*cos(2*v)
sinus
X=sin(2+u)
Y=u
Z=1
helix
X=2*v*sin(v)
Y=1
Z=v*cos(2*v)
0<=U<=2*pi
0<=V<=4*pi
![](https://elearning.rcub.bg.ac.rs/moodle/pluginfile.php/28762/mod_forum/attachment/31531/k.jpg)